POWER ASYMMETRIES IN PEATLAND RESTORATION: A POLITICAL ECOLOGY PERSPECTIVE ON MULTI-STAKEHOLDER PARTICIPATION IN THE MENDAHARA–BATANGHARI PEAT HYDROLOGICAL UNIT - Pangeran Putra Perkasa Alam Nasution; Amiruddin Ketaren; Yuli Santri Isma; Rakhmadsyah Putra Rangkuty (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Peatland ecosystems play a strategic role in global climate change mitigation through their capacity for carbon sequestration and hydrological regulation. However, peatland degradation in Indonesia demonstrates that environmental degradation is not merely an ecological issue but is also closely associated with power dynamics, public policies, and political-economic interests. This study aims to examine the dynamics of multi-stakeholder participation in peatland restoration and to analyse how power relations influence the effectiveness of restoration policy implementation within the framework of the peat hydrological unit. A qualitative research approach employing a participatory action research (PAR) design was adopted. Data were collected through participant observation, in-depth interviews, focus group discussions (FGDs), and document analysis in the Mendahara–Batanghari peat hydrological unit, Jambi Province, Indonesia. The data were analysed using thematic analysis integrated with a political ecology perspective to examine power relations and conflicts of interest among stakeholders. The findings reveal that multi-stakeholder participation in peatland restoration remains largely procedural rather than substantive, as decision-making processes continue to be dominated by government institutions and corporate actors. Although local communities possess high legitimacy and valuable ecological knowledge, they remain marginalised due to limited access to resources and decision-making power. Furthermore, conflicts between economic development objectives, particularly the expansion of oil palm plantations and the ecological goals of peatland restoration, constitute a major obstacle to the effectiveness of restoration programs. Peatland degradation is rooted in unequal power structures and broader political-economic processes that facilitate resource exploitation. Co-management-based multi-stakeholder participation that emphasises power redistribution, the strengthening of local institutions, and the integration of ecosystem-based policies through the peat hydrological unit framework is expected to enhance the long-term effectiveness of peatland restoration while promoting more equitable, inclusive, and sustainable natural resource governance.